Students Difficulties in Determining Case in Sentence - Adha, Ruly; Nishrina, Syifa (JL3T (Journal of Linguistics, Literature and Language Teaching), 2021)
The objectives of this research were to find out the students difficulties in determining types of case and to investigate the reasons why the students had difficulties in determining case. This was a qualitative descriptive research. The subject of this research was the sixth semester students of English Department in IAIN Langsa that consist of 30 students. Documentation, questionnaire and interview were the instruments in collecting the data. Based on the data, the students felt difficult in determining types of case such as accusative, locative, nominative, possessive, agentive, and ablative. It can be seen from the mistakes made by students through documentation and supported by the results obtained from questionnaire and interview. Then, there were several reasons why the students had difficulties in determining case. They were: 1) Many types of case given by a lecturer made the students difficult to remember them. 2) The students were confused with the types of case because a noun phrase can have more than one type. 3) The students felt difficult to distinguish between accusative and dative case. 4) The students did not master English grammar well.